2019
DOI: 10.1111/jog.14052
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding and treatment of intra‐amniotic infection with Ureaplasma spp.

Abstract: Considerable evidence has shown that intra-amniotic infection with Ureaplasma spp. increases the risk of chorioamnionitis and preterm labor. Ureaplasma spp. are among the smallest organisms, and their isolation is uncommon in routine clinical practice because of their size and high auxotrophy. Although Ureaplasma spp. have been reported as causative agents of preterm birth, they also have a high incidence in vaginal swabs collected from healthy reproductive-age women; this has led to questions on the virulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 109 publications
(115 reference statements)
1
24
0
Order By: Relevance
“…Based on the available data, mycoplasmas utilize three mechanisms for degrading Ig. The first mechanism is the secretion of IgA protease, as reported in U. urealyticum and U. parvum, which participates in facilitating microorganism colonization and host immune system evasion on the mucosal surface by proteolytic activity against IgA 1 [15,[138][139][140]. The second mechanism is retaining the Ig binding protein and Ig protease (MIB-MIP) system to degrade IgG.…”
Section: Immunoglobulin Proteasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the available data, mycoplasmas utilize three mechanisms for degrading Ig. The first mechanism is the secretion of IgA protease, as reported in U. urealyticum and U. parvum, which participates in facilitating microorganism colonization and host immune system evasion on the mucosal surface by proteolytic activity against IgA 1 [15,[138][139][140]. The second mechanism is retaining the Ig binding protein and Ig protease (MIB-MIP) system to degrade IgG.…”
Section: Immunoglobulin Proteasesmentioning
confidence: 99%
“…Other potential pathogenic effects of NH 3 production including fatal hyperammonemia syndrome and the formation and precipitation of struvite in the urinary tract [200,201]. A study also showed that the urease activity of U. urealyticum was higher than that of U. parvum [15], suggesting that U. urealyticum may trigger more severe localized pathological damage.…”
Section: Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Ureaplasma spp. are frequently isolated from the amniotic fluid and placentas of preterm infants [1,2] and have been associated with adverse prenatal outcomes such as miscarriages, preterm labor, preterm premature rupture of membranes, and chorioamnionitis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a cell wall confers resistance to all β-lactam and glycopeptide antibiotics. On the other hand, the lack of de novo synthesis of folic acid makes the cells resistant to diaminopyrimidines and sulfonamides (Beeton & Spiller, 2016;Tantengco & Yanagihara, 2019). Many authors emphasize that the development of resistance of Ureaplasma spp.…”
Section: Introductionmentioning
confidence: 99%